Cloning and Production of Antigen 85A Mycobacterium tuberculosis for Diagnostic Latent Tuberculosis: a Preliminary Study - Agus, Rosana; Sjafaraenan; Samara, Yulianti; Massi, Muhammad Nasrum (HAYATI Journal of Biosciences, 2024)
The main challenge in the management of Tuberculosis (TB) is diagnosing quickly and accurately, especially Latent Tuberculosis Infection (LTBI). LTBI detection was carried out using the Tuberculin Skin Test (TST) and Interferon Gamma Release Assay (IGRA). In TB endemic areas, these two examinations have limitations, so current research is directed at finding specific antigens for the diagnosis of LTBI. One of the potential proteins is Antigen 85A (Ag85A) Mycobacterium tuberculosis (Mtb) encoded by Fibronectin-binding protein A (FbpA). The Ag85 complex induces the proliferation of T-cells and interferon-gamma in most healthy individuals infected with Mycobacterium tuberculosis, Mycobacterium leprae, and BCG-vaccinated mice, making it a potential antigen. This study aims to clone and produce recombinant protein Ag85A from Mtb in Escherichia coli BL21. The methods used were ligation to the pET-32a expression vector, transformation to Escherichia coli BL21, and production of protein by IPTG induction. Characterization of recombinant clones by colony PCR and sequencing. The results obtained were that the fbpA gene isolated from Mtb clinical isolate had been amplified, and the PCR product was 900 bp. The production of Antigen 85A has been successfully carried out and produces 44 kDa.